Scarless vocal fold regeneration by urine-derived stem cells and small intestinal submucosa hydrogel composites through enhancement of M2 macrophage Polarization, neovascularization and Re-epithelialization - Juan-Juan Hu; Xiong-Xin Lei; Yan-Lin Jiang; Chen-Yu Zou; Yu-Ting Song; Chen-Yu Wu; Lin-Qiao Tang; Dan Lu; Jesse Li-Ling; Hui Yang; Hui-Qi Xie (Smart Materials in Medicine, 2022)
Vocal fold (VF) scarring is a major etiology of voice disorders and a leading cause for permanent intractable dysphonia. To date, several approaches have been used to address VF injury and scarring, which included scar excision and biomaterial injection and/or implantation. Despite the considerable research progress made in this field, these have not been established as routine clinical procedures due to various restrictions. Tissue engineered scaffolds for delivering growth factors in vivo and implementation of simultaneous delivery of multi-potent cells may achieve better outcome. In this study, we have developed Urine-derived stem cells - Small intestinal submucosa hydrogel composites (USCs@SIS), which are injectable and capable of sustaining the survival and metabolism of the USCs in the scarred VF. The three-dimensional complex showed a robust ability of anti-inflammatory polarization, neovascularization, re-epithelialization and anti-fibrosis in a rabbit model for heat-injured VFs. In vitro experiment proved that the hydrogel composites could promote polarization of M2 macrophages, tube formation by human umbilical vein endothelial cells, proliferation and migration by human bronchial epithelial cells, and suppression of differentiation of human fetal lung fibroblasts and human primary fibroblast cells of VF. Application of the USCs@SIS thereby may overcome the substantial limitations of the current strategies for scarless VF regeneration.